2015
DOI: 10.5114/pjp.2015.53012
|View full text |Cite
|
Sign up to set email alerts
|

Original paper Epstein-Barr virus DNA in colorectal carcinoma in Iranian patients

Abstract: Colorectal cancer is an often fatal cancer with a rapidly increasing incidence. Current mortality is estimated to be approximately 600,000 per year, and both environmental and genetic factors are involved in its etiology. Viral and bacterial factors have a proven role in the incidence of approximately 20% of cancers. In the present study, the Epstein-Barr virus (EBV) was detected in 50 colorectal adenocarcinomas, 12 colon adenomas, and 38 control tissue samples using polymerase chain reaction (PCR). Epstein-Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…In conclusion, we hereby show that EBV is present in human CRC in the Syrian population. In addition, EBV infection was detected in approximately 36% of CRC samples, which is similar to its presence in CRC specimens worldwide 28,31,47 including the Middle Eastern region, as reported by Tafvizi et al 32 Additionally, we demonstrate that the presence of EBV in CRC is associated with more aggressive malignancy phenotype. However, further studies are required to elucidate the exact role and pathogenesis of EBV in human malignancy and the importance of the upcoming EBV vaccine.…”
Section: Tested Cases Ebv-positive Percentagesupporting
confidence: 89%
See 2 more Smart Citations
“…In conclusion, we hereby show that EBV is present in human CRC in the Syrian population. In addition, EBV infection was detected in approximately 36% of CRC samples, which is similar to its presence in CRC specimens worldwide 28,31,47 including the Middle Eastern region, as reported by Tafvizi et al 32 Additionally, we demonstrate that the presence of EBV in CRC is associated with more aggressive malignancy phenotype. However, further studies are required to elucidate the exact role and pathogenesis of EBV in human malignancy and the importance of the upcoming EBV vaccine.…”
Section: Tested Cases Ebv-positive Percentagesupporting
confidence: 89%
“…More importantly, we were able to show that E6/E7 onco-proteins of high-risk HPV type 16 convert non-invasive and non-metastatic human cancer cells into invasive and metastatic ones. 27 Regarding the presence of EBV in CRC worldwide, several recent investigations reported that 20-50% of these cancer cases are positive for EBV [28][29][30][31][32] ; however, a small number of studies were unable to detect EBV in colorectal carcinomas but in their infiltrated lymphomas. 33,34 Meanwhile, it is important to emphasize that the presence of EBV in the Middle East region is limited to 2 conflicting studies from Iran, as Tafvizi et al, 32 revealed that 38% (19/50) of human CRC cases are positive for EBV in the Iranian population; however, the second study was unable to detect the presence of EBV in only 15 CRC samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in situ hybridization method is more sensitive than [29,30].Whereas LMP1 was reported as the major oncogenic factor of nasopharyngeal carcinoma (NPC) development and was detected in 80%-90% of NPC tumors [31,32]. This indicates that, these proteins are essential for EBV to immortalize B cells and to transform other types of cells, such as rodent fibroblasts, by changing transcription and sustainable activation of the cell signaling pathway [33]. Our study focuses on the prevalence of EBVaGC, so there is no data on patients follow up however it is very useful in further study.…”
Section: Discussionmentioning
confidence: 99%
“…Most positive studies revealed EBV positivity rate to bẽ 20-40% of the cases. 20,23,26,29,30,32,34 A study of Salyakina et al 26 reported a common co-infection of EBV with other viruses in 20% of the CRC samples (Cytomegalovirus and Human Herpesvirus 6B/HHV-6B/). An interesting case study by Chang et al 28 on collision colorectal tumors (adenocarcinoma and non-Hodgkin lymphoma) revealed serum EBV positivity.…”
Section: Status Of Ebv In Colorectal Cancermentioning
confidence: 99%